2006
DOI: 10.1002/ceat.200500267
|View full text |Cite
|
Sign up to set email alerts
|

Operability of an Industrial Catalytic Naphtha Reformer in the Presence of Catalyst Deactivation

Abstract: Bifunctional naphtha reforming catalysts are deactivated by side reactions such as coking, sintering, and poisoning in the course of industrial operation. This results in a reduction of the octane number of the product in a commercial naphtha reforming unit. Catalyst deactivation is compensated for by increasing the operating temperature so that the primary product yields are kept constant during an operating cycle. In the present study, a deactivation model has been developed for industrial catalytic naphtha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…However, by application of a catalyst deactivation model [38], this conventional model has been also validated by comparison of the theoretical and experimental data for 800 operating days. This comparison has been presented in Table 3.…”
Section: Model Validationmentioning
confidence: 99%
“…However, by application of a catalyst deactivation model [38], this conventional model has been also validated by comparison of the theoretical and experimental data for 800 operating days. This comparison has been presented in Table 3.…”
Section: Model Validationmentioning
confidence: 99%
“…Therefore, it was essential to compensate the deactivation effect by increasing the inlet temperature of reactors versus DOS. For an industrial catalytic naphtha reformer, it was reported that the variations of RON versus days on stream was an appropriate index to show the activity of the catalyst [33]. Consequently, to identify the activity of Pt-Re/Al2O3 catalyst, a set of ninety-seven data points during 919 days obtained from the target reforming plant.…”
Section: Naphtha Catalytic Reforming Modelmentioning
confidence: 99%
“…Many correlations have been proposed to model catalyst deactivation. The catalyst deactivation model employed is that proposed by Rahimpour (2006).…”
Section: Catalyst Deactivation Modelmentioning
confidence: 99%
“…In order that the calculated parameters be comparable with those of Rahimpour (2006), the reference temperature, T0, is selected to be equal to 770 K. Each reactor is divided into 40 weight intervals such that in each interval the amount of catalyst activity is constant and is function of time and catalyst temperature. Reaction rate in each interval is obtained by Eq.…”
Section: Catalyst Deactivation Modelmentioning
confidence: 99%
See 1 more Smart Citation